Turbocharging vaccines: emerging adjuvants for dendritic cell based therapeutic cancer vaccines. (August 2017) - Saxena, Mansi; Bhardwaj, Nina
Graphical abstract: All adjuvants that play a role in carrying the vaccine cargo to the lymph nodes (LNs) such as nanoparticles, self-polymerizing platforms and albumin binding platforms are in essence targeting LN-DCs. On the other hand, oncolytic viruses recruit and activate intra-tumoral DCs. TLR and STING agonists serve to instigate and maintain DC activation ex vivo and in vivo . There are adjuvants that directly influence DC proliferation and recruitment such as, FLT3L and GM-CSF. C type lectin receptor (CLR) agonists, CD40Ls, and Saponin based adjuvants (SBAs) promote specific DC targeting and cross-presentation. Highlights: Antigen presentation by Dendritic cells to both CD4 and CD8 + T cells is the cornerstone of successful vaccines. Vaccine adjuvants are critical for overcoming cancer related immunosuppression. All adjuvants target DCs directly or indirectly. Advances in conventional adjuvants and advent of new adjuvants for cancer therapy. Formulating multiple adjuvants in one vaccine platform and combination with checkpoint blockade immunotherapy. Abstract : Development of therapeutic cancer vaccines has been hindered by the many pro-tumorigenic mechanisms at play in cancer patients that serve to suppress both antigen presenting cells and T cells. In face of these obstacles, cancer vaccines are most likely to promote anti-tumorigenic immune responses only when formulated with strong adjuvants, and in combination with new immune interventions designed to reverse immune suppression and exhaustion of T cells in the tumor microenvironment. Dendritic cells (DCs) are often termed 'nature's adjuvant' due to their exceptional capacity for initiating both innate and adaptive immune responses. Hence, the past decade has witnessed a flurry of activity in testing DC based immunotherapies for cancer intervention. In this review we will discuss advances in conventional adjuvants and provide insight into new adjuvants as they pertain to DC cancer therapy.